Contextual Learning-Based E-Student’s Worksheet for Grade VI Elementary School - Anak Agung Dwi Mas Juliastari; I Made Citra Wibawa; I Gede Astawan (Universitas Pendidikan Ganesha, 2022)
There are still many teachers who have difficulty in making appropriate learning tools for students. It has an impact on learning activities that are not running optimally. This research aims to develop an E-Student’s Worksheet based on contextual learning of the characteristics of living things and their environment. This type of research is R&D using the ADDIE model. The subjects of this study consisted of 2 media experts and 2 material experts, research trial were 1 teacher/practitioner and 10 fifth-grade students. The data collection methods were observation, interviews, and questionnaires. The instrument used is a rating scale. The data analysis technique used in this research is the descriptive qualitative analysis and descriptive quantitative analysis. The results of the study are the scores obtained based on the assessment of learning media experts, coloring with a value of 5.00 (very valid), the display of E-Student’s Worksheet is 4.33 (Valid), and Presentation of 5.00 (very valid). The average value of E-Student’s Worksheet media validation from media experts is 4.78 (very valid). The overall result of the average validation of the material is 4.66, therefore the material presented on the E-Student’s Worksheet is very valid. The teacher's assessment results are 95% (very practical), and the student's assessment results are 92.2% (very practical). It is concluded that contextual learning-based E-Student’s Worksheet is feasible to use in the learning process because it can help students understand the material and motivate them to learn well.